Assessing Financial Literacy of Female Entrepreneurs in Informal Economy: Empirical Evidence from Micro Business in Malaysia - Mohd Noor, Nurul Hidayana; Md Zaini, Syeliya; Omar, Noralina; Mohd Beta, Raja Mayang Delima; Wei, Chang Lee (Information Management and Business Review, 2024)
Financial management in business ensures that the goals of an organization are achieved. It has become a priority for every business to have good financial resources to ensure sustainability. However, many entrepreneurs are found to need help managing their finances well and are used to supporting a lavish lifestyle. As an outcome, they had to take a personal loan from a financial institution, and this personal loan is a big commitment because they must pay it back with a high loan rate. This situation puts an additional burden on entrepreneurs, which eventually becomes the cause of business failure. Employing a mixed method, this study’s objectives are to evaluate the financial literacy of female entrepreneurs of micro-businesses in Malaysia and to determine the causes of financial illiteracy. This study involved 100 female entrepreneurs in the survey study and 20 female entrepreneurs of micro business in the interview study. The survey data were examined using descriptive and inferential statistics, and interview data were analyzed using thematic analysis. The survey findings have revealed that most female entrepreneurs have a low level of financial literacy, and financial literacy significantly influences business success. Interview data revealed that most informants still need to adopt the systematic accounting system, are unable to organize financial and personal accounts, do not have proper financial savings, and cannot calculate product costing and selling price. Therefore, this study will help female entrepreneurs manage their future financial practices.